Nursing care practices for people with Chronic Noncommunicable Diseases - Becker,Renata Machado (2018)
ABSTRACT Objective: To understand care practices for people with Chronic Noncommunicable Disease, developed by Primary Health Care nurses in a municipality in southern Brazil. Method: Qualitative study, developed through the Discourse of the Collective Subject. Twenty-three nurses from the Family Health Strategy participated. Data were collected through semi-structured interviews and analyzed by the health promotion framework. Results: Nurses care practices for people with chronic disease present themselves through the home visit, individual care and collective care. These, eventually, have an extended character, advocating the promotion of health, at other times it is restrictive, returning to be a traditional and biologicalist practice. Final considerations: The nurse acts in a diversified way in this field, being present in the lives of people with chronic diseases. However, it is necessary to move forward, especially in the search for the constant and continuous development of an extended and welcoming care practice.